Multi-Electrode EMG Spatial-Filter Implementation Based on Current Conveyors - Guerrero, Federico Nicolás (2024)
In this work, a circuit topology for the implementation of a multi-electrode superficial electromyography (EMG) front-end is presented based on a type II current conveyor (CCII). The presented topology provides a feasible way to implement an amplifier capable of measuring several electrode locations and obtaining the signal of interest for posterior acquisition. In particular, a five-electrode normal double differential (NDD) EMG spatial filter is demonstrated. The signal modes necessary for the analysis of the circuit are derived, the respective rejection ratios are obtained, and the noise characteristic is calculated. A board-level electrode is implemented as a proof of concept, achieving a gain equal to 28 dB, a bandwidth of 17 Hz to 578 Hz, a noise voltage linked to the input of 3.7 uVrms and a common-mode rejection ratio higher than 95 dB at interference frequencies. The topology was validated after using it as an active electrode in experimental EMG measurements with an NDD dry-contact electrode in a flexible printed circuit board.